2010
DOI: 10.1177/0310057x1003800219
|View full text |Cite
|
Sign up to set email alerts
|

Compartment Syndrome and Patient-Controlled Analgesia in Children – Analgesic Complication or Early Warning System?

Abstract: We present two cases of children who developed compartment syndrome after upper limb fractures. Morphine patient-controlled analgesia was used in a bolus-only mode for analgesia (bolus 20 μg/kg, five minute lockout and hourly limit of 150 μg/kg). An increase in patient-controlled analgesia use was observed up to 12 hours before the decision was made to proceed to fasciotomy but neither child exceeded the hourly limit or had an excessive increase in pain scores. Clinical risk factors for compartment syndrome sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…A recent editorial also suggested that PEA does not delay diagnosis of compartment syndrome (27). Is it also true that morphine techniques may also mask the diagnosis of compartment syndrome if settings are not optimum (28).…”
Section: Compartment Syndromementioning
confidence: 99%
“…A recent editorial also suggested that PEA does not delay diagnosis of compartment syndrome (27). Is it also true that morphine techniques may also mask the diagnosis of compartment syndrome if settings are not optimum (28).…”
Section: Compartment Syndromementioning
confidence: 99%
“…Careful titration of morphine dosage in patient/parent-controlled analgesia has also been recommended as a tool in raising the suspicion of CS in patients on narcotic analgesia. 70 Open fractures can still develop CS 71 and the presence of a wound does not automatically decompress a compartment. It should not be forgotten that CS can also develop after surgical intervention and limb should be carefully monitored in postintervention period.…”
Section: Compartment Syndromementioning
confidence: 99%
“… 3 Early recognition and treatment with an emergent fasciotomy is crucial, as the risk of complications such as muscle necrosis, 4 , 5 neurological deficits, 3 , 5 , 6 delayed fracture union, 7 Volkmann ischemic contraction, 8 myoglobinuria, 8 10 renal failure, 8 12 and potentially death 10 , 11 , 13 increases as time of tissue anoxia elapses. 14 17 The diagnosis of CS is clinical and requires a high index of suspicion. 6 , 18 , 19 Classical symptoms of CS include pain, 13 , 20 – 25 pallor, 25 , 26 paresthesias, 20 , 24 , 25 , 27 pulselessness, 24 and paralysis.…”
Section: Introductionmentioning
confidence: 99%